A giant villous adenoma case mimicking right colon carcinoma - Mahmut C. YAĞMURDUR; Feride ALEVLİ and Gürden GÜR and Nihan HABERAL and Gökhan MORAY and Sedat BOYACIOĞLU and Mehmet HABERAL (Turkish Journal of Gastroenterology, 2019)
-